STUDI KOMPARASI POLA PENULISAN BERITA FEATURE PADA MEDIA ONLINE LIPUTAN6.COM DAN TRIBUNSUMSEL.COM - Fitria Fitria; Hamidah Hamidah; Anang Walian (Tabayyun: Journal of Journalism, 2020)
ABSTRACK News writing can be conveyed in various types of writing, depending on what style the journalist or media wants to apply. These various styles of information delivery lead to various types of news, one of which is feature news. The existence of feature news is used as a media as a distraction for readers after reading hard news. In addition, the function of a media is not only to provide information for readers but also as a means of entertaining the audience, so that the features should be present to please and inspire readers. Therefore, researchers are interested in raising the title, "Comparative Study of Featured News Writing Patterns in Online Media Liputan6.com and TribunSumsel.com" as research material. This study aims to find the similarities and differences in the feature news writing patterns applied to the online media Liputan6.com and TribunSumsel.com. This study uses a feature structure pattern analysis approach to Andi Baso Mappatoto's theory which has four types, namely, inverted pyramid, ordinary pyramid, rectangular pyramid and chronological pyramid. The methodology used in this research is a comparative study method which is a qualitative descriptive model. Collecting data using the method of observation, interviews, and collecting documents in the form of writing human interest features and scientific features on both online media. The results showed that the human interest news feature Liputan6.com applied a rectangular pyramid building pattern with story intro composition, thematic paragraph patterns and summary closings, while in the media TribunSumsel.com applied a rectangular pyramid building pattern with a summary intro composition, block paragraph patterns and climax closings. In the scientific features in the Liputa6.com media, it uses a chronological pyramid building pattern consisting of a summary intro, a chronological paragraph pattern and a climax closing, while Tribunsumsel.com still uses a rectangular building pattern composed of summary intros, thematic paragraph patterns and climax closings. Keyword: Patterns, News, Feautures, Media, Online Media